PENURUNAN PARAMETER KEKERUHAN, TSS DAN TDS DENGAN VARIASI UNIT FLOKULASI - Edhi Sarwono; Khairunnisa Rizky Aprillia; yunianto Setiawan (Mulawarman University Press, 2017)
AbstractA research on water treatment at Mahakam River water using the gravel bed flocculator (medium grained), the variation of theflocculation units gravel bed using granular media are used in the form of pieces of PVC pipe 1